Is Repetition Really the Key to Success? The Impact of Ad Repetition and the Power of "Likes" on Facebook. Issue 3 (2nd September 2022) - Lim, Hyunjoo; Bright, Laura F.; Wilcox, Gary B.
Abstract: In today's marketplace, social media advertising, such as Facebook ads, are an especially valuable tool for small and medium-sized enterprises (SMEs), which are often financially volatile due to their limited access to resources, as well as political, economic, and social factors. The purpose of this article is to help SMEs better understand how to develop an advertising strategy on Facebook that is mindful of their time and resources. The findings of this article suggest that social media ad frequency, specifically on Facebook, leads to website visits, and social media engagement metrics (i.e., post shares and comments) can strengthen this relationship. Website visits, in turn, are suggested to increase the likelihood of purchases made during visits, and longer durations of visits can strengthen this relationship. This research contributes to our knowledge of Facebook advertising effects by examining behavioral trace data generated by consumers engaging with SMEs. By examining real-time consumption patterns, this research provides immediate managerial implications that can be employed by SMEs as they develop Facebook marketing plans for the future.